1998
DOI: 10.1143/jjap.37.1721
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Effects due to Grain and Grain Boundary Traps in Laser Annealed Poly-Si Thin Film Transistors

Abstract: A new physical model based on two dimensional simulations for high quality laser re-crystallised poly-Si thin film transistors is presented. It has been shown that to adequately explain the improved subthreshold slope and the lack of saturation of the output characteristics in these transistors, it is essential to distribute the density of defect states between traps in the grains alongside traps localised at grain boundaries. A double exponential density of states has been extracted for thin film tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 17 publications
2
25
1
Order By: Relevance
“…However, it has been observed that subthreshold and output characteristic of field-effect transistors are difficult to model in this approximation. 41 Therefore, we would like to assume that the grain boundary has a negligible thickness compared to the grain size L and contains a concentration n t of traps at an energy E t localized at the grain boundary. 42 ͑Similar to the bulk trapping this discrete level may be replaced by a trap distribution.͒ Now, the influence of the grain boundary traps is not only determined by ⌰, more importantly the charge at the grain boundary determines the barrier height E B at the grain.…”
Section: Grain Boundariesmentioning
confidence: 99%
“…However, it has been observed that subthreshold and output characteristic of field-effect transistors are difficult to model in this approximation. 41 Therefore, we would like to assume that the grain boundary has a negligible thickness compared to the grain size L and contains a concentration n t of traps at an energy E t localized at the grain boundary. 42 ͑Similar to the bulk trapping this discrete level may be replaced by a trap distribution.͒ Now, the influence of the grain boundary traps is not only determined by ⌰, more importantly the charge at the grain boundary determines the barrier height E B at the grain.…”
Section: Grain Boundariesmentioning
confidence: 99%
“…Although there has been research to analyze the grain-boundary in poly-Si TFTs, [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] this article analyzes the dependence on the grain-boundary location, following a brief report by the authors. 42 Figure 1 shows the structure of a poly-Si TFT for twodimensional ͑2D͒ device simulation.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally agreed that for biasstress-induced shifts in poly-Si TFTs, power-law exponents in the range of 0.1-0.3 are indicative of hot-carrier injection, whereas power-law exponents in the range of 0.4-0.6 are indicative of deep-state generation, presumably at crystal-domain boundaries [6], [10], [11]. Accordingly, in this letter we have used the power-law expression shown in (1) to fit the and degradation and extract the value of the exponent " " as a function of film thickness and gate-bias stressing voltage.…”
Section: Methodsmentioning
confidence: 99%